Synovial sarcoma in children and adolescents: Thirty three years of experience with multimodal therapy - (:unkn) unknown (WILEY-LISS, 2001)
Background. Synovial sarcoma (SS) is the most common type of non-rhabdomyosarcoma soft tissue sarcoma in childhood with controversies about its prognosis and treatment. Procedure. We reviewed medical records of 42 children and adolescents with SS treated at our institution between 1966 and 1999 to determine treatment results and assess prognostic factors. Results With a median follow-up duration of 7.8 years (range 0.2-22.4 years), 5-year progression free survival (PFS) and overall survival (OS) rates were 75.6% (95% Confidence Interval [CI] 62-89.2%) and 87.7% (95% CI 77.3-98.1%) respectively. Eleven patients were dead and four others had progressed but were alive without evidence of disease after further therapy. IRS grouping and tumor invasiveness were found to be significant prognostic indicators (P < 0.01 and = 0.02, respectively). Patients with initial gross total resection (IRS I and II) and non-invasive tumors (T1) were most likely to have prolonged PFS and OS. Patients with small tumors (< 5 cm) (P = 0.09) or with monophasic histology (P = 0.14) had better PFS and OS. Conclusions. Achieving a complete resection or gross total resection with microscopic residual disease is vital for survival of patients with localized SS. Patients with localized disease who received radiotherapy had improved local control. Chemotherapy did not seem to impact PFS or OS. Future large mufti-institutional trials are needed to address whether post-operative chemotherapy is necessary for patients with localized, surgically removed tumors, whether radiotherapy is necessary for patients with completely resected tumors, and to ascertain the order of importance of all the candidate prognostic markers. Med Pediatr Oncol 2001;37: 90-96. (C) 2001 Wiley-Liss, Inc.
Keywords: synovial sarcoma; childhood cancer; soft tissue sarcoma; RESEARCH-HOSPITAL EXPERIENCE; SOFT-TISSUE; IDENTIFICATION; METASTASES; FUSION; TUMORS; GENES; SYT; SSX